1996
DOI: 10.1111/j.1745-4522.1996.tb00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclopropenoid Fatty Acids (Baobab Seed Oil) on the Fatty Acid Profile of Lipids From Different Tissues in the Rat

Abstract: Rats were fed for 8 weeks a diet containing either Baobab seed oil (FBO) rich in cyclopropenoid fatty acids (CPFA) or heated oil (HBO) devoid of CPFA. In FBO rats, compared to controls (CO), the monounsaturated fatty acid content of adipose tissue lipids, liver triacylglycerols, liver and adrenal cholesteryl esters and liver, kidney, adrenal phospholipids were highly decreased to the benefit of saturated fatty acid content. In cholesteryl esters and phospholipids, the arachidonic acid (20:4 n‐6) content was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Previous studies have been inconclusive as to the effect of cyclopropenoid fatty acids on the activity of other fatty acid desaturases. Although it was originally suggested that they had no effect on D6 desaturase activity (19), subsequent studies have questioned this (21,22). In the present study, there was a small increase in hepatic C18:2 associated with SO feeding.…”
Section: Discussionsupporting
confidence: 39%
“…Previous studies have been inconclusive as to the effect of cyclopropenoid fatty acids on the activity of other fatty acid desaturases. Although it was originally suggested that they had no effect on D6 desaturase activity (19), subsequent studies have questioned this (21,22). In the present study, there was a small increase in hepatic C18:2 associated with SO feeding.…”
Section: Discussionsupporting
confidence: 39%
“…It has been suggested that they play both antifungal () and antifeedant () roles. The presence of these acids can interfere with fatty acid desaturases in animals that include cottonseed products in their diet ( ). In poultry, inclusion of cottonseed products in feed causes discoloration of the egg yolk ( , ).…”
Section: Introductionmentioning
confidence: 99%